OnabotulinumtoxinA for the Treatment of Patients with Overactive Bladder and Urinary Incontinence: Results of a Phase 3, Randomized, Placebo Controlled Trial - Nitti, Victor W; Dmochowski, Roger; Herschorn, Sender; Sand, Peter; Thompson, Catherine; Nardo, Christopher; Yan, Xiaohong; Haag-Molkenteller, Cornelia (The Journal of urology, 2017)
Overactive bladder affects 12% to 17% of the general population and almost a third experience urinary incontinence, which may severely impact health related quality of life. Oral anticholinergics are the mainstay of pharmacological treatment but they are limited by inadequate efficacy or side effects, leading to a high discontinuation rate. We report the results of the first large (557 patients), phase 3, placebo controlled trial of onabotulinumtoxinA in patients with overactive bladder and urinary incontinence inadequately managed with anticholinergics. Eligible patients with overactive bladder, 3 or more urgency urinary incontinence episodes in 3 days and 8 or more micturitions per day were randomized 1:1 to receive intradetrusor injection of onabotulinumtoxinA 100 U or placebo. Co-primary end points were the change from baseline in the number of urinary incontinence episodes per day and the proportion of patients with a positive response on the treatment benefit scale at posttreatment week 12. Secondary end points included other overactive bladder symptoms and health related quality of life. Adverse events were assessed. OnabotulinumtoxinA significantly decreased the daily frequency of urinary incontinence episodes vs placebo (-2.65 vs -0.87, p <0.001) and 22.9% vs 6.5% of patients became completely continent. A larger proportion of onabotulinumtoxinA than placebo treated patients reported a positive response on the treatment benefit scale (60.8% vs 29.2%, p <0.001). All other overactive bladder symptoms improved vs placebo (p ≤0.05). OnabotulinumtoxinA improved patient health related quality of life across multiple measures (p <0.001). Uncomplicated urinary tract infection was the most common adverse event. A 5.4% rate of urinary retention was observed. OnabotulinumtoxinA 100 U showed significant, clinically relevant improvement in all overactive bladder symptoms and health related quality of life in patients inadequately treated with anticholinergics and was well tolerated.